GAMBARAN KECEMASAN PADA PASIEN PRA-OPERASI DI RSUD BULELENG - Sugiartha, Putu Agus; Juniartha, I Gusti Ngurah; Kamayani, Made Oka Ari (Coping: Community of Publishing in Nursing; Vol 9 No 3 (2021): Juni 2021, 2021)
Anxiety is interpreted as a response to certain threatening situations and conditions that are normal, which are influenced by intrinsic and extrinsic factors. This study aims to describe the anxiety of pre operative patients in RSUD Buleleng. The design of this research is quantitative research with descriptive research design with cross sectional approach. Respondents in this study were as many as 90 pre operative patients treated in the Kamboja room who were determined by consecutive sampling technique. Data collection was done using the Hamilton Anxiety Ratting Scale (HARS) questionnaire to measure anxiety. Based on the data analysis carried out can be obtained an illustration that respondents experienced severe anxiety levels 6 (6.70%) respondents, moderate anxiety 22 (24.40) respondents, mild anxiety 42 (46.70%) respondents and densest 20 (22.20 %) respondents did not experience anxiety. It is recommended to use the results of research to always be able to pay attention and be able to manage the anxiety experienced before surgery by pharmacology or by non pharmacology.